Prevalence and prognosis of hypoxia‐inducible factor‐2α (HIF‐2α) pathway gene mutations across advanced solid tumors - Zhong, Wenjun; Ma, Jiemin; Chen, Cai; Dettman, E. J.; Cristescu, Razvan; Naik, Girish S.; Jin, Fan; Shao, Changxia (Cancer medicine (Malden, MA), 2024)
Introduction Hypoxia‐inducible factor‐2α (HIF‐2α) modulates the hypoxic response pathway in tumors; however, mutations in pathways (including SDHA, SDHB, SDHC, SDHD, FH, and VHL genes) that are suspected to activate HIF‐2α are poorly understood, with limited understanding of the prevalence and clinical prognosis. Methods This retrospective observational study used a de‐identified nationwide (US‐based) clinico‐genomic database (CGDB) across 15 available tumor types. Results Among the 9467 adult patients with advanced/metastatic solid tumors included in the analysis, any mutation at the above‐mentioned six genes was observed in 1.8% (95% CI: 1.5–2.1) of patients. The mutation prevalence ranged from 0.05% of SDHD to 0.93% of VHL. When further stratified by tumor type, the prevalence of gene mutation in each tumor type was well below 1%, except for VHL with 44% in renal cell carcinomas (RCC). Excluding RCC, the prevalence of any HIF‐2α gene mutations in the study population was 0.9% (95% CI: 0.8–1.2). The median overall survival (OS) from 1 and 2 L therapy among patients with any HIF‐2α gene mutation was 14.5 (95% CI: 11.5–24.2) and 9.3 (95% CI: 6.0–18.1) months, respectively, compared with 13.4 (95% CI: 12.9–13.9) and 9.8 (95% CI: 9.3–10.4) months among patients without HIF‐2α gene mutations. Discussion and Conclusions The prevalence of HIF‐2α related gene mutations was generally low (<1%) across the 15 solid tumor types, except for VHL in RCC. No significant association between HIF‐2α gene mutation status and OS was identified among patients evaluated in this study.